A multiple criteria decision making technique for supplier selection and inventory management strategy: A case of multi-product and multi-supplier problem - Parhizkari, Morteza; Amirib, Maghsoud; Mousakhani, Morteza (Decision Science Letters, 2013)
Selection of an appropriate supplier along with planning a good inventory system has become an area of open research for the past few years. In this paper, we present a multi objective decision making supplier and inventory management model where two objectives including the quality and offering price of supplier are minimized, simultaneously. The proposed model is formulated as mixed integer programming and it is converted into an ordinary single objective function using Lp-Norm. In order to find efficient solution, we use NSGA-II as meta-heuristic technique and the performance of the proposed model is examined using some instances. The preliminary results indicate that both Lp-Norm and NSGA-II methods can be used to handle problems in various sizes.